Human motion analysis and its application in sports and sport medicine - Dolná, Zlatica; Šimšík, Dušan; Majerník, Jaroslav; Galajdová, Alena (Lékař a technika, 2008)
The paper presents an overview of the systems used for human motion analysis and a brief description of their application. We use optical motion capture system SMART from e-Motion, BTS based on detection of small passive refl ex markers, to analyze subjects' movements in our studies. Th e aim is to estimate and assess movement, abilities in pathological cases evaluated in clinical fi eld, e.g. rehabilitation, gait analysis utilisation, stability disorders and also in sports medicine. Th e application of the system SMART is set to laboratory conditions for recording exercises, monitoring of performance, evaluation of motion abilities, development of individual skills, training of correct and/or optimal trajectories and to ensure the feedback. Th is exact approach is more precise than commonly applied methods based on subjective visual analysis and brings objectivization and quantifi cation of human motion that is very signifi cant also in sports and sport medicine.
Keywords: financování organizované; Track and Field; Movement; monitorování fyziologických funkcí; pohyb; sporty; Human Experimentation; Monitoring, Physiologic; Sports Medicine; pohybová aktivita; postura těla; lidé; elektromyografie; Electronic Data Processing; automatizované zpracování dat; Video Recording; Financing, Organized; Electromyography; experimenty na lidech; tělovýchovné lékařství; Sports; Posture; Motor Activity; audiovizuální záznam; lehká atletika; Humans